Formulation of plant nutrient with synbiotic enhancement - Ananthan, S. P. V.; Ahmad, N.; Noor, S. H.; Mimi Sakinah, A. M.; Alias, S.; Hamid, H.; Mohammed, M.; Romli, A. (Universiti Malaysia Pahang, 2021)
Oleochemical wastewater discharge from the industry into water sources is one of the main causes of water pollution. A proper treatment is required before the effluent is discharged to the environment. Since the oleochemical wastewater contains nutrients and probiotics that are good for plants, it could be used as a nutrient provider for the plants instead. Therefore, the formulation of synbiotic plant nutrients from this effluent is an effective way of using the oleochemical effluent. This study aimed to formulate the plant nutrients by using industrial wastewater, which contains the synbiotic enhancement and validating the significance of the formulated plant nutrients into three types of plants; Abelmoschus esculentus (Okra), Solanum Melongena (Brinjal), and Capsicum annuum (Chilli peppers). Synbiotic is a combination of both prebiotics and probiotics that benefit the host by stimulating the growth of a limited number of health-promoting bacteria. To formulate the plant nutrient, the wastewater was filtered using a cotton cloth before the pre-biotics solution was added. Sample A (filtered wastewater was mixed with Sample B (prebiotics solution) by different percentages, namely F1 (100%:0%), F2 (75%:25%), F3 (50%:50%), F3 (25%:75%), 0%:100% (Sample A to Sample B respectively) and lastly, 50%:50% (Sample C (unfiltered wastewater) to Sample B respectively). The height of the plant and the number of leaves are measured weekly for four months. From the data, it can be seen that F3 gave significant results for the okra plant, in which it gains the highest height of plant compared to the other two plants. On the other hand, F6 give the best results for both the brinjal and the chilli plant where their leaves grow the highest from the second until the fourth month of plant growth. Hence, this research gives an added value to the wastewater, whereas the wastewater is used as the synbiotic plant nutrient enhancer and work best for the plants.